Efektifitas Analisis Teknikal Moving Average Convergence Divergence (MACD) dan Relative Strength Index (Rsi) dalam Menentukan Sinyal Jual dan Sinyal Beli Saham IDX30 - Muhammad Resky Fahrullah; Abdi Akbar Idris; Anwar Anwar (Trending: Jurnal Manajemen dan Ekonomi, 2025)
This research aims to find out the accuracy of determining sell signals and buy signals of IDX30 shares by using Moving Average Convergence Divergence (MACD) and Relative Strength Index (RSI). The type of research used is qualitative descriptive. The population in this study includes stocks listed in the IDX 30 index for the period of May 2023-May 2024, while the sample in this study is 8 company shares collected using purposive sampling techniques. The data collection technique used is the documentation method. The collected data was analyzed using stocks that experienced golden cross and death cross for MACD and stocks that experienced overbought and oversold for RSI then put into the (W) Sign Test. The research results show that the MACD and RSI technical analysis indicators are accurate in predicting the direction of the resulting stock price movement. Thus, this research provides the accuracy of MACD and RSI technical analysis indicators in predicting the direction of stock price movements. which is included in the IDX30 index.